Implementasi Media Tiga Dimensi Kemagnetan Berbasis Inkuiri Melalui Strategi Kooperatif Terhadap Sikap Ilmiah Siswa - Ahmad Harjono; Wahab Jufri; Kurniawan Arizona (Department of Physics Education, Universitas Mataram, 2015)
The aim of this study was to determine the influence of the integrated MTDKBI through cooperative strategies for studentsÃ¢â¬â¢scientific attitude. The study used quasi-experiment method with a 2x2 factorial design research. The population was 380 students of grade 9 SMPN 10 Mataram whose spread.at 10 classes. The sample was 142 students divided into 4 classes with cluster random sampling technique. The research instruments such as questionnaires of scientific attitude which was given at the beginning and the end of the study. The data were analyzed with two-way Ancova. The results showed that (1) the students who learned using MTDKBI significantly different at the aspect of scientific attitude than students who learned with non MTDKBI, (2) students who learn through STAD cooperative strategy significantly different at the aspect of scientific attitude than students who learn with NHT type, (3) there is an interaction effect between the type of media with cooperative strategies for students' scientific attitude